1988
DOI: 10.1177/030006058801600306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Breath Operated Powder Inhaler

Abstract: A randomized, double-blind, double-dummy crossover study on 42 asthmatics was carried out to compare the single dose effects of salbutamol administered from the widely used metered dose inhaler and a breath operated system (Diskhaler). The bronchodilator response (change in forced expiratory volume in the first second) was almost identical for the two systems. The Diskhaler system however, since it is breath operated, obviates the need for hand-breath coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Inspiratory flow-driven dry powder inhalers (DPI) have been shown to be safe and effective means of drug delivery in the inhalation therapy [3, 4]. Easyhaler (EH) is a novel multidose DPI for the treatment of obstructive lung diseases such as asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Inspiratory flow-driven dry powder inhalers (DPI) have been shown to be safe and effective means of drug delivery in the inhalation therapy [3, 4]. Easyhaler (EH) is a novel multidose DPI for the treatment of obstructive lung diseases such as asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have demonstrated pharmacodynamic similarity between inhaled products using FEV I (Pover et al 1988;Ruffin et al 1989), PEFR (Hartley et al 1977;Tukiainen & Terho 1985;Zainudin et al 1990) and a combination of FEV I and MEFR (Zanen et al 1992). The last-named study highlights the need for guidelines because although FEV 1 values were similar after inhalation of different products, there was a significant difference between MEFR values recorded 60 minutes after each dose.…”
Section: Pharmacodynamic Methodsmentioning
confidence: 96%
“…If a study is performed at only one dose level for each of the devices, it is not possible to verify that the response is on the slope of the dose-response curve if no difference between the two ways of administering the drug is observed. Unfortunately, many of the studies presented in the literature [8,[72][73][74][75][76][77][78] have an inadequate design and are, thus, inconclusive. A well-designed comparative study should include at least two dose levels, for at least one of the devices, and it is necessary to show a difference in the response between the two dose levels to draw conclusions.…”
Section: Airway Effectsmentioning
confidence: 99%
“…In spite of an inconclusive design, the effect of 200 µg salbutamol delivered via a pMDI was claimed to be equivalent to 400 µg delivered via Diskhaler® when using a single-dose design [8]. Autohaler® has been compared to an ordinary pMDI in a single-dose study [75].…”
Section: Salbutamolmentioning
confidence: 99%
See 1 more Smart Citation